THE PROCESS OF STUDENT COGNITION IN CONSTRUCTING MATHEMATICAL CONJECTURE - I Wayan Puja Astawa; I Ketut Budayasa; Dwi Juniati (Journal on Mathematics Education, 2018)
This research aims to describe the process of student cognition in constructing mathematical conjecture. Many researchers have studied this process but without giving a detailed explanation of how students understand the information to construct a mathematical conjecture. The researchers focus their analysis on how to construct and prove the conjecture. This article discusses the process of student cognition in constructing mathematical conjecture from the very beginning of the process. The process is studied through qualitative research involving six students from the Mathematics Education Department in the Ganesha University of Education. The process of student cognition in constructing mathematical conjecture is grouped into five different stages. The stages consist of understanding the problem, exploring the problem, formulating conjecture, justifying conjecture, and proving conjecture. In addition, details of the process of the students’ cognition in each stage are also discussed.DOI: http://dx.doi.org/10.22342/jme.9.1.4278.15-26